Data for: Halogens in serpentinites from the Isua supracrustal belt, Greenland: an Eoarchean seawater signature and biomass proxy? - D'Andres, J (via Mendeley Data) (2020)
This dataset contains whole rock major and trace element geochemistry, mineral chemistry, zircon U-Pb isotopes and trace element data, as well as noble gases and halogens concentrations of Eoarchean serpentinites from the Isua supracrustal belt. THIS DATASET IS ARCHIVED AT DANS/EASY, BUT NOT ACCESSIBLE HERE. TO VIEW A LIST OF FILES AND ACCESS THE FILES IN THIS DATASET CLICK ON THE DOI-LINK ABOVE